The prognostic impact of surufatinib for the treatment of advanced pancreatic ductal adenocarcinoma: a single center real-world retrospective study - Yang, Yanzhen; Xie, Qu; Shang, Chuankai; Jiang, Lai; Ding, Guojun; Long, Dan; Luo, Cong (Frontiers in Oncology, 2025)
BackgroundPancreatic ductal adenocarcinoma (PDAC) is a highly aggressive tumor with a poor prognosis, despite the emergence of chemotherapies such as gemcitabine plus albumin-bound paclitaxel (nab-paclitaxel, AG), unmet medical needs still exist for patients with metastatic PDAC (mPDAC). Surufatinib is a small-molecule tyrosine kinase inhibitor targets vascular endothelial growth factor (VEGFR) 1, 2, 3, fibroblast growth factor receptor 1 (FGFR1), and colony stimulating factor 1 receptor (CSF-1R). This single-center, retrospective study evaluates the potential efficacy of combination therapy containing Surufatinib in advanced or metastatic pancreatic cancer.MethodWe conducted a real world retrospective study of mPDAC patients who received the Surufatinib between July 2022 and July 2023 at Zhejiang Cancer Hospital. In addition, patients who received first line chemotherapy at the same period were analyzed as comparison.ResultAs of November 20, 2024, 20 eligible patients were identified in this retrospective study. The median progression-free survival (mPFS) of patients who received Surufatinib treatment was 5.27 months (95% CI, 2.55–7.98), and the median overall survival(mOS) was 9.93 months (95% CI,6.55-13.32). For fist line treatment, 9 patients received Surufatinib combined with immune checkpoint inhibitors (ICIs) and chemo and the mPFS was 7.5 months (95% CI, 3.14–11.85), compared with an mPFS of 5.43 months (95% CI, 3.89-6.96) for 52 mPDAC patients received chemotherapy at the same period. Grade 3 or above Treatment Related Adverse Event (TRAE) were neutrophil count decreased (10%), and white blood cell count decreased (5%).ConclusionPreliminary data suggest that surufatinib shows potential therapeutic benefit in mPDAC, but its efficacy needs to be further validated. This combination strategy may provide a new treatment option for patients, especially in the first-line setting. Future studies will expand the sample size and include additional evaluation parameters to fully assess its efficacy and safety.Clinical trial registrationClinicalTrials, identifier NCT06378580